Potensi Limbah Padat Kelapa Sawit Sebagai Sumber Energi Terbarukan Dalam Implementasi Indonesian Sustainability Palm Oil - M Imam Arifandy; Eka Pandu Cynthia; Sarbaini sarbaini; Fitriani Muttakin; Nazaruddin Nazaruddin (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2021)
In 2019 Indonesia became the largest producer of Crude Palm Oil / CPO in the world, with a total area of oil palm plantations reaching 14,456,611 hectares with Crude Palm Oil / CPO production reaching 47,120,247 tons. The CPO production process produces various kinds of waste, one of which is solid waste. If the waste is not managed properly, it will cause environmental problems. This study aims to calculate the potential for managing waste generated from palm oil mills, namely solid waste as a renewable energy source and the potential effect of palm oil solid waste on increasing the value of Net Energy Balance (NEB) and the value of Net Energy Ratio (NER). This study uses a quantitative approach by performing calculations using the Life Cycle Assessment (LCA) method which is used to calculate the balance of the solid waste produced by the palm oil mill, which is then converted into energy factor values from accountable literature sources. The calculation results show that for each processing of 1 ton of fresh fruit bunches (FFB) of oil palm, it produces 130 kg of fiber waste and 65 kg of kernel shell waste. The results show that if solid waste is applied as an alternative fuel to the boiler, it will be able to produce 13,182 MJ of energy. This renewable energy source can increase the value of NEB from 27,199 MJ to 40,378.01 MJ (48.45%) and increase NER from 3.19 to 4.01 or an increase of 25.7%.